Economic Significance of Palm Tree Viroids - Vadamalai, Ganesan; Rodriguez, Judith; Randles, J. W. (Elsevier Inc, 2017)
The ongoing epidemic of the lethal cadang-cadang disease in the Philippines, caused by coconut cadang-cadang viroid (CCCVd), has killed around 40 million (Mn) coconut palms over the last century. A survey in 2012–13 showed that the boundary of cadang-cadang distribution has not expanded markedly over recent decades. The current incidence is about 700,000 diseased palms and rate of spread is predicted to continue at 0.1%–1.0% per annum. Orange leaf-spotting (OS), a nonlethal disorder of oil palm, is associated with infection by variants of CCCVd. OS has a yield penalty of 25%–50% on individual palms, and overall incidence is estimated to be 1%–5%. Malaysia earns approximately $17.24 billion annually from the oil palm industry, and the national loss from OS is estimated at $25.6–256.2 Mn. Provision of CCCVd-free planting material for new plantations is advocated for raising the yield potential of oil palm. The lethal tinangaja disease, caused by coconut tinangaja viroid, remains an uncontrolled disease of coconut palms in Guam.